2015
DOI: 10.3171/2014.10.jns141624
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sinonasal quality of life and nasal morbidity after fully endoscopic transsphenoidal surgery

Abstract: OBJECT Despite the increasing application of endoscopic transsphenoidal surgery for pituitary lesions, the prognostic factors that are associated with sinonasal quality of life (QOL) and nasal morbidity are not well understood. The authors examine the predictors of sinonasal QOL and nasal morbidity in patients undergoing fully endoscopic transsphenoidal surgery. METHODS An exploratory post hoc analysis was conducted of patients who underwent endoscopic pituitary surgery and were enrolled in a prospective mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 18 publications
6
80
0
Order By: Relevance
“…There are only 2 Level 1 studies on sinonasal‐related QOL outcomes following ESBS, both by Little et al., both studies focused on pituitary lesions. One study found that there was no difference in nasal morbidity and QOL outcomes between microscopic and endoscopic approaches .…”
Section: Complicationsmentioning
confidence: 99%
“…There are only 2 Level 1 studies on sinonasal‐related QOL outcomes following ESBS, both by Little et al., both studies focused on pituitary lesions. One study found that there was no difference in nasal morbidity and QOL outcomes between microscopic and endoscopic approaches .…”
Section: Complicationsmentioning
confidence: 99%
“…12,14,47) Sinonasal QOL following endoscopic pituitary surgery reaches a nadir at 2 to 3 weeks and recovers by 6 weeks to 3 months postoperatively. 4951) Sinonasal QOL and overall health status are well correlated in the postoperative period, suggesting the importance of sinonasal QOL on the patient experience. 49) Many authors noted better sinonasal QOL after endoscopic approach than microscopic approach at least in short-term period after surgery.…”
Section: Complicationsmentioning
confidence: 99%
“…4951) Sinonasal QOL and overall health status are well correlated in the postoperative period, suggesting the importance of sinonasal QOL on the patient experience. 49) Many authors noted better sinonasal QOL after endoscopic approach than microscopic approach at least in short-term period after surgery. 4954) However, Pledger et al 51) reported that although patients who underwent endoscopic surgery experienced significantly fewer nasal symptoms during the first 8 weeks, by 1 year after surgery, there were no significant differences between the endoscopic and microscopic groups.…”
Section: Complicationsmentioning
confidence: 99%
“…The endonasal approach may result in temporary side effects such as sinusitis and nasal crusting. The longer‐term side effects/complications of EESBS include anosmia/hyposmia, synechiae, chronic sinusitis, and cosmetic changes from excessive septal resection or removal of the piriform aperture . Finally, the field of vision in EESBS is limited to an anterior aspect only.…”
Section: Resultsmentioning
confidence: 99%